Aspek Regulasi dan Kewenangan Penegakan Hukum Pajak Reklame - Tinara Aisyah Nikita; Adhitya Widya Kartika (Jurnal Kajian Pembaruan Hukum, 2021)
The Mayor's Regulation Number 21 of 2018 licenses procedure and other matters that the taxpayer must obey. This study analyzed the effectiveness of law enforcement on the late-payment of advertisement tax in Surabaya. This study used empirical legal research that observed the effectiveness of the law in society and how the law works in society. The data collected were from documentation from literature and legislation, observation in the community, and interviews with related parties. It showed that law enforcement was effective but with several obstacles experienced in enforcing the law. In particular, it dealt with the COVID-19 pandemic as the challenge that required new conditioning according to the recommendations from the central government. This study concluded that the law enforcement of billboard tax payments in Surabaya is quite effective due to the achievement of tax revenue targets that always reach the target. However, there are still many obstacles faced, and several solutions deal with these obstacles. KEYWORDS: Advertisement Tax, Billboard Tax, Law Enforcement, Tax, Surabaya.